Cho hàm số $$f(x)=\begin{cases}
\dfrac{\sqrt{x^2+1}-1}{x} &\text{khi }x\neq0\\
0 &\text{khi }x=0
\end{cases}$$Tính \(f'(0)\).
\(f'(0)=0\) | |
\(f'(0)=1\) | |
\(f'(0)=\dfrac{1}{2}\) | |
Không tồn tại |
Chọn phương án C.
\(\begin{aligned}
f'(0)&=\lim\limits_{x\to0}\dfrac{f(x)-f(0)}{x}\\
&=\lim\limits_{x\to0}\dfrac{\dfrac{\sqrt{x^2+1}-1}{x}-0}{x}\\
&=\lim\limits_{x\to0}\dfrac{\sqrt{x^2+1}-1}{x^2}\\
&=\lim\limits_{x\to0}\dfrac{\left(\sqrt{x^2+1}-1\right)\left(\sqrt{x^2+1}+1\right)}{x^2\left(\sqrt{x^2+1}+1\right)}\\
&=\lim\limits_{x\to0}\dfrac{\left(x^2+1\right)-1}{x^2\left(\sqrt{x^2+1}+1\right)}\\
&=\lim\limits_{x\to0}\dfrac{x^2}{x^2\left(\sqrt{x^2+1}+1\right)}\\
&=\lim\limits_{x\to0}\dfrac{1}{\sqrt{x^2+1}+1}\\
&=\dfrac{1}{2}.
\end{aligned}\)